Una aproximación al pensamiento de Humberto Giannini. - Acevedo, Jorge (Revista Chilena de Humanidades, 2016)
This study places Prof. Humberto Giannini’s intellectual undertaking in .the area of the "philosophy of existence". lt also synthesizes as well as systematizes the thematic variety found in the publications of this Chilean thinker. A ohecklist of .those works consulted for the present study is included.